Peran Harga dan Citra Merek dalam Mediasi Pengaruh E-Word to Mouth terhadap Keputusan Pembelian melalui Aplikasi TikTok - Prasetyo Harisandi; Adibah Yahya; Renny Risqiani; Purwanto Purwanto (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Currently, people in Indonesia need a way to shop that is easy and also reliable. The existence of the TikTok application is the answer to this problem in addition to its main function as an entertainment application that can be used with the Android or IOS application operating system. This study aims to determine whether price, brand image affect purchase intention by e-Word of Mouth mediation in using the TikTok application. This research method uses a quantitative approach by distributing questionnaires to 130 consumers as measured by a scale of 1 to 5. Smart PLS (Partial Least Squares) is used in the analysis of this study to test external and internal models. The results of this study indicate that price, brand image have a significant impact on purchase intention. Through mediation variables e-Word of Mouth. So that the TikTok application can answer consumer questions and problems, simplify, and increase daily purchases. Nowadays, people need a way to shop that is easy, with prices and products that are suitable to save time and additional costs.